Komunikasi budaya masyarakat Pandai Sikek dalam melakukan transformasi pengetahuan lokal - Erza, Elfitri Kurnia; Yusup, Pawit M.; Erwina, Wina (Universitas Padjadjaran, 2017)
The âPandai Sikekâ weaving activity is a form of cultural communication through the maternal line (matrilineality) which upholds values and norms. Values and norms of the âsongketâ culture are governed by the peopleâs belief that there was an ancestral sacred oath. The local people make information fosters the development of knowledge. This promotes the transformation of knowledge as a form of local knowledge development of the Pandai Sikek community which is fully supported by the community and by the use of media as well. The purpose of this study was to look at the communication pattern of the weaver, employer and government in the transformation process of local knowledge. The research method used was qualitative with ethnographic approach. The main data were collected by unstructured interview, observation and documentation study. The communication pattern among weavers was circular, involving experience, information sharing, application, knowledge, and innovation. Study results indicated the existence of a pattern by the weaverâs community, were experiences shared through information sharing, and then applied to create knowledge. The use of knowledge would result in innovation and then became an experience again.Â Entrepreneurs became the bridge for cooperation to support the economy of society. The government issued a policy of protection and knowledge preservation through HAKI (Intellectual Property Rights). In conclusion, the transformation of knowledge continues to develop the socio-economic life of society containing values, norms, and beliefs, which has been performed from generation to generation.